Physiological and biomechanical responses between seated and standing positions during distance-based uphill time trials in elite cyclists - Bouillod, A.; Grappe, F. (Journal of Sports Sciences, 2018)
Cyclists regularly change from a seated to a standing position when the gradient increases during uphill cycling. The aim of this study was to analyse the physiological and biomechanical responses between seated and standing positions during distance-based uphill time trials in elite cyclists. Thirteen elite cyclists completed two testing sessions that included an incremental-specific cycling test on a cycle ergometer to determine VO2max and three distance-based uphill time trials in the field to determine physiological and biomechanical variables. The change from seated to standing position did not influence physiological variables. However, power output was increased by 12.6% in standing position when compared with seated position, whereas speed was similar between the two positions. That involved a significant increase in mechanical cost and tangential force (Ftang) on the pedal (+19% and +22.4%, respectively) and a decrease (-8%) in the pedalling cadence. Additionally, cyclists spent 22.4% of their time in the standing position during the climbing time trials. Our findings showed that cyclists alternated between seated and standing positions in order to maintain a constant speed by adjusting the balance between pedalling cadence and Ftang.